Prognostic score predicts overall survival following complete urinary tract extirpation. (2nd January 2020) - Akand, Murat; Muilwijk, Tim; Van Der Aa, Frank; Gevaert, Thomas; Milenkovic, Uros; Moris, Lisa; Blyweert, Wim; Van Poppel, Hendrik; Albersen, Maarten; Joniau, Steven
Abstract: Purpose: To evaluate the oncological outcome and complications of patients treated with complete urinary tract extirpation (CUTE) in our department, and to identify prognostic factors for survival. Methods: Clinico-pathological data of patients treated with one-step or stepwise CUTE between 1999 and 2017 were collected retrospectively. Complications were classified according to the modified Clavien–Dindo classification (CDC) in the early (≤30 days) and late (>30 days) follow-up. Log-rank test was used to assess independent predictors of overall survival (OS), cancer-specific survival (CSS) and recurrence-free survival (RFS). Results: Twenty-five patients (20 male) underwent CUTE (16 one-step) for BC + unilateral/bilateral UTUC. Minor (CDC 1-2) and major (CDC3-5) complications were observed in 72% and 40% of patients, respectively, in the early postoperative period (≤30 days). Five (20%) patients died in the perioperative period (CDC 5) with a median OS of 52 days (range: 25–77). Median time to last follow-up or death was 30 months (range: 0–161). Median OS was 50 months (95% Confidence Interval [CI]: 22–118 months), while median CCS and RFS were not reached. The 5-year OS, CSS and RFS were 42.7%, 69.6% and 66.7%, respectively. A score for determining which patients would benefit from CUTE was arbitrarily developed, and showed that the patients with a score of 0–2 points (good prognosis) had a better OS than the patients with a poor prognosis (3–4 points) in the log-rank test. Conclusions: Because of lower OS rates, patients with ESRD or with a CUTE score of 3–4 points are probably not ideal candidates for CUTE.